Rediseño de Terminal Terrestre del cantón Quevedo provincia de Los Ríos con implementación de arquitectura industrializada - Mora Vélez, Diana Nicole (2023)
This research study focuses on analyzing the visual impact that could result from the redesign of the Quevedo land terminal, located in the province of Los Ríos. The main objective is to improve the user experience by providing quality service and satisfaction. To achieve this, an exhaustive analysis of the current state of the terminal will be carried out, evaluating key aspects such as its infrastructure, organization, distribution, and quality of materials that currently make up the terminal. The analysis will identify areas for improvement and guide the redesign decisions, focusing on offering a more modern and efficient experience. One of the proposals is the use of industrialized materials, which will not only add a touch of modernity, but could also improve the functionality and durability of the terminal....